1962
DOI: 10.1139/m62-062
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Rhizosphere Microflora of Citrus Trees: Ii. Qualitative Distribution of the Bacterial Flora

Abstract: Studies were made on the relative incidence of various morphological, physiological, and nutritional groups of bacteria in the rhizosphere regions of growing and non-growing roots of three species of Citrus as compared to those in the soil. Gram-negative non-sporing rods were more abundant in the rhizospheres of both growing and non-growing roots than in the soil, whereas Gram-positive rods, cocci, and sporefor~ners were more numerous in the soil than in the rhizospheres. Nitrate reducers, gelatin liquefiers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1963
1963
2012
2012

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…However, another study conducted by Rangaswami and Vasantharajan ( 1962a ) showed that the fungi number was 3-6 times in the rhizospheres of the three 6-year-old citrus species in the Annamalai University Experimental Orchard than in soils, actinomycetes 2-6 times, and bacteria 40-90 times. However, sulfur-oxidizing bacteria were absent in citrus rhizosphere (Rangaswami and Vasantharajan 1962b ) . There was no signi fi cant difference of rhizosphere microorganisms among the three Citrus species, though the fungal population in the rhizosphere of the citrus variety Pummelo was slightly higher than that in the other two varieties (Rangaswami and Vasantharajan 1962a ) .…”
Section: Rhizosphere Microbial Populationmentioning
confidence: 96%
“…However, another study conducted by Rangaswami and Vasantharajan ( 1962a ) showed that the fungi number was 3-6 times in the rhizospheres of the three 6-year-old citrus species in the Annamalai University Experimental Orchard than in soils, actinomycetes 2-6 times, and bacteria 40-90 times. However, sulfur-oxidizing bacteria were absent in citrus rhizosphere (Rangaswami and Vasantharajan 1962b ) . There was no signi fi cant difference of rhizosphere microorganisms among the three Citrus species, though the fungal population in the rhizosphere of the citrus variety Pummelo was slightly higher than that in the other two varieties (Rangaswami and Vasantharajan 1962a ) .…”
Section: Rhizosphere Microbial Populationmentioning
confidence: 96%